At the intersection of exocytosis and endocytosis in plants. Issue 4 (4th August 2019) - Zhang, Liang; Xing, Jingjing; Lin, Jinxing
Summary: Vesicle exocytosis and endocytosis control the activities and turnover of plasma membrane proteins required for signaling triggering or attenuating at the cell surface. In recent years, the diverse exocytic and endocytic trafficking pathways have been uncovered in plants. The balance between conventional and unconventional protein secretion provides an efficient strategy to respond to stress conditions. Similarly, clathrin‐dependent and ‐independent endocytosis cooperatively regulate the dynamics of membrane proteins in response to environmental cues. In fact, many aspects of plant growth and development, such as tip growth, immune response, and protein polarity establishment, involve the tight deployment of exo–endocytic trafficking. However, our understanding of their intersection is limited. Here, we discuss recent advances in the molecular factors coupling plant exo–endocytic trafficking and the biological significance of balance between exocytosis and endocytosis in plants.